Faktor-faktor yang mempengaruhi nasabah menabung di lembaga perkreditan desa (LPD) kawasan pemukiman dan pariwisata - Ni Made Dhita Kusuma Wahyuni; I Nyoman Gede Ustriyana; Gede Mekse Korri Arisena (Fakultas Pertanian Universitas Yudharta Pasuruan, 2020)
Local credit institutions (LPD) are non-bank financial institutions manager by local governments and are autonomous and oriented to strengthen the economic and socio-cultural life of indigenous peoples in Bali. This study aims to analyze what factors influence the customer's decision to save in the LPD of residential and tourism areas and analyze what are the dominant factors that influence the customer's decision to save in the LPD of residential areas and tourism. The data used using primary data as the main data by distributing questionnaires in each LPD as many as 50 respondents. The data obtained were processed using SPSS and SEM-PLS analysis techniques. The results showed that factors such as the environment of the customer's residence significantly influence the interest in saving in the LPD of residential areas and security guarantees affect the interest in saving customers in the LPD of the tourism area.